Deficiency in pigment epithelium‐derived factor accelerates pulmonary growth and development in a compensatory lung growth model. Issue 10 (27th September 2021) - Ko, Victoria H.; Yu, Lumeng J.; Secor, Jordan D.; Pan, Amy; Mitchell, Paul D.; Kishikawa, Hiroko; Puder, Mark
Abstract: Children with hypoplastic lung disease associated with congenital diaphragmatic hernia (CDH) continue to suffer significant morbidity and mortality secondary to progressive pulmonary disease. Recently published work from our lab demonstrated the potential of Roxadustat (FG‐4592), a prolyl hydroxylase inhibitor, as a treatment for CDH‐associated pulmonary hypoplasia. Treatment with Roxadustat led to significantly accelerated compensatory lung growth (CLG) through downregulation of pigment epithelium‐derived factor (PEDF), an anti‐angiogenic factor, rather than upregulation of vascular endothelial growth factor (VEGF). PEDF and its role in pulmonary development is a largely unexplored field. In this study, we sought to further evaluate the role of PEDF in accelerating CLG. PEDF‐deficient mice demonstrated significantly increased lung volume, total lung capacity, and alveolarization compared to wild type controls following left pneumonectomy without increased VEGF expression. Furthermore, Roxadustat administration in PEDF‐deficient mice did not further accelerate CLG. Human microvascular endothelial lung cells (HMVEC‐L) and human pulmonary alveolar epithelial cells (HPAEC) similarly demonstrated decreased PEDF expression with Roxadustat administration. Additionally, downregulation of PEDF in Roxadustat‐treated HMVEC‐L and HPAEC, a previously unreported finding, speaks to the potential translatability of Roxadustat from small animal studies. Taken together, these findings further suggest that PEDF downregulation is the primary mechanism by which Roxadustat accelerates CLG. More importantly, these data highlight the critical role PEDF may have in pulmonary growth and development, a previously unexplored field.